POTENSI EDIBLE FILM ANTIMIKROBA SEBAGAI PENGAWET DAGING - Maskiyah (Maskiyah); Juniawati (Juniawati); Evi Savitri Iriani (Faculty of Animal Science, Universitas Gadjah Mada, 2015)
Fresh meat are highly perishable due to their enriched nutrient composition which is easily contaminated by almost any microorganisms. The application of antimicrobial edible films is one of the effective method to extend the shelf life of fresh meat. This study aimed to get antimicrobial edible films formula that have the potential to preserve fresh meat. The study consisted of several steps: 1) research for making a fresh garlic extract, 2) extraction of gelatin from chicken feet, 3) formulation and manufacturing of antimicrobial edible films and 4) the application of edible films on fresh meat. Gelatin-based antimicrobial edible films was the best one that can be applied on fresh meat. Characteristics of the antimirobial edible film: color L 97.28; elongation: 20 mm; tensile strength <0.1 kgf; thickness 0.06 mm; WVTR 15.49 g/(mm.jam); Aw 0.526; moisture content: 22.73%, and has antimicrobial characteristic because of it’s inhibition ability to the growth of S. aureus and E. coli.(Key words: Antimicrobial, Edible film, Meat)